Akademisyenlerin Meslek Ahlakına Aykırı Olan Davranışlara İlişkin Algıları (Çomü Eğitim Fakültesi Örneği) Academicians’ Perceptions Of Behaviours Against Occupational Ethics (A Case In Comu, Faculty Of Education) - MAYA, İlknur (Turkish Studies, 2018)
This study aims at determining what academicians consider to beagainst ethics in activities that they perform (such as educationalactivities, research and social service) and their causes as well as howto prevent them. It also makes an attempt at identifying the dilemmasacademicians might have concerning ethics. The research uses a semistructuredinterview technique, one of the qualitative research methods.The research group was composed of the 50 subjects chosen throughsnowball sampling from the 100 academicians group working in theFaculty of Education in Canakkale Onsekiz Mart University. Inductiveanalysis, a type of content analysis, was conducted in the analysis ofthe data. The behaviours that the academicians considered to beagainst occupational ethics were mostly related with educationalactivities, and second mostly related with research activities. Theacademicians consider refusing to teach with no excuse, coming toclass late without an excuse/ leaving the classroom early, notconducting the instruction effectively and qualitatively, failing to fulfillthe responsibilities at university due to working outside the University,not treating students equally / fairly against professional ethics most interms of educational-instructional activities. They consider not givingthe quotations and resources correctly, not conducting high quality andoriginal research studies and making changes in the research dataunproffessional most in terms of research- related activities. Besides,they find doing nothing for social service against professional ethics interms of service to the society. The causes for such behaviours werelisted as personal characteristics, desiring to promote quickly and timeinsuffiency, economic insuffiency, and institutional expectations. Theacademicians stated that those behaviours could be prevented throughthe formation of an institutional culture, having role-models amongadministrators especially and among employees, the formation of aninstitutional infrastructure, ethic values of an institution, questioningone’s conscience, values education and character education, andregular supervision. It was found that academicians experienced ethicaldilemmas between educational activities and research activities,between their work at university and willingness to work in privatesector, and between administrators’ pressures and their personal valuesin fulfilling their duties; respectively. Araştırmada, akademisyenlerin gerçekleştirdikleri eğitim-öğretim, araştırma ve topluma hizmet gibi etkinliklerde meslek ahlakına aykırı olarak algıladıkları davranışların neler olduğunun, nedenlerinin ve nasıl önlenebileceğinin belirlenmesi amaçlanmaktadır. Ayrıca çalışmada, akademisyenlerin yaşadıkları etik ikilemlerin neler olduğunun saptanmasına çalışılmaktadır. Araştırmada nitel araştırma yöntemlerinden yarı yapılandırılmış görüşme tekniği kullanılmıştır. Çalışma grubunu, Çanakkale Onsekiz Mart Üniversitesi Eğitim Fakültesinde görev yapmakta olan yüz akademisyenden kartopu örnekleme yoluyla seçilmiş elli kişi oluşturmaktadır. Verilerin analizinde, içerik analizi türlerinden tümevarımcı analiz kullanılmıştır. Akademisyenlerin meslek ahlakına aykırı olarak algıladıkları davranışlar, en çok eğitim-öğretim işleri daha sonra araştırma işlerinde görülmektedir. Akademisyenler, eğitim-öğretim işleri bakımından en çok mazeretsiz ders yapmamak, mazeretsiz derse geç girmek / dersten erken çıkmak, dersi etkili ve nitelikli olarak yürütmemek, üniversite dışında çalışma nedeniyle üniversitedeki sorumluluklarını yerine getirmemek ve öğrencilere eşit / adil davranmamak davranışlarını meslek ahlakına aykırı bulmaktadır. Akademisyenler, araştırma işleri bakımından en çok araştırmada alıntı ve kaynakları doğru vermemek, nitelikli ve özgün araştırmalar yapmamak ve araştırma verileri üzerinde oynamak davranışlarını meslek ahlakına aykırı bulmaktadır. Akademisyenler, topluma hizmet işleri bakımından topluma hizmet anlamında hiçbir çalışma yapmamak davranışını meslek ahlakına aykırı bulmaktadır. Akademisyenlerin meslek ahlakına aykırı olarak algıladıkları davranışların nedenleri, en çok sırasıyla kişisel özellikler, kısa zamanda yükselme isteği ve zaman yetersizliği, ekonomik yetersizlikler ve kurumsal beklentilerdir. Akademisyenler, meslek ahlakına aykırı olarak algıladıkları davranışların kurumsal kültürün oluşması, yöneticilerin ve çalışanların rol model olması, kurumsal alt yapının olması, kurumun etik değerlerinin olması, vicdani sorgulama, değerler ve karakter eğitimi ve düzenli denetimlerle önlenebileceğini belirtmektedir. Akademisyenler, görevlerini yerine getirirken en çok sırasıyla eğitim-öğretim işleri ve araştırma işleri, üniversitedeki görevleri ve özel sektörde görev alma ve yöneticilerin baskısı ve kişisel değerleriarasında tercih yapma durumunda ahlaki ikilem yaşamaktadır.